The Role of Transformational Leadership in Improving Organisational Performance: A Human Resource Management Perspective - Taufiq Hidayah (International Journal of Economics (IJEC), 2025)
This study explores the role of transformational leadership in enhancing organizational performance from a Human Resource Management (HRM) perspective. Utilizing qualitative methods, including semi-structured interviews and focus group discussions with 30 participants across various industries, the research identifies key themes that illustrate how transformational leadership behaviors influence employee motivation, job satisfaction, organizational commitment, and innovation. Findings reveal that visionary leadership fosters a shared sense of purpose, while empowerment and trust enhance employee engagement and ownership. Intellectual stimulation encourages creativity and collaboration, contributing to an innovative culture. Furthermore, supportive HRM practices, such as leadership development programs and performance management systems, are crucial in nurturing transformational leaders. The results underscore the significant impact of transformational leadership on organizational effectiveness and highlight the importance of strategic HRM initiatives in cultivating leaders who can inspire teams to achieve shared goals. This research contributes to the understanding of effective leadership dynamics within organizations and offers practical implications for HRM practices aimed at fostering high-performance cultures.